Education Policy and the Australian Education Union Resisting Social Neoliberalism and Audit Technologies - Vandenberg, Andrew (Springer International Publishing, 2018)
This book focuses on the politics of teacher resistance to the formation and implementation of neoliberal education policies in Australia. It argues that policies such as publishing examination test results online amounts to auditing teachers' work, and assumes incompetence from teachers, which ultimately results in diverting teachers from their true professional responsibilities. The book outlines the rise of transnational networks that promote market-oriented methods of achieving social objectives, such as good education for all students, and considers a range of explanations for why this education policy was strengthened in Australia in 2010. It also reviews a range of arguments about professional unionism, and reflects on the history of the Australian Education Union and its capacity to resist social neoliberalism. The book concludes by reporting on a case-study in which principals, teachers and parents at two ordinary schools in Australia have managed to keep market forces at bay. It will appeal to students and researchers in the fields of education and sociology, particularly those interested in education policy, political ideology, unionism, and schools. Andrew Vandenberg is Senior Lecturer in Politics and Policy Studies at Deakin University, Australia, in the School of Humanities and Social Sciences. He researches issues related to the politics of unionism, social movements, and democratisation in Sweden, Australia, and Indonesia, and is author of Democracy and Citizenship in a Global Era.